2004
DOI: 10.1023/b:anto.0000024911.67625.27
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterisation of lipoglycan macroamphiphiles from Propionibacterium acnes

Abstract: Lipidated macroamphiphiles such as the lipoteichoic acids and mycobacterial lipoarabinomannans are cell envelope components of Gram-positive bacteria that have been extensively associated with the pathogenesis of disease. In order to study such associations, purification of these macroamphiphiles is essential for resolving their structures and diverse biological effects. We describe herein a method for purification of lipoglycan components from Propionibacterium acnes. This method uses the existing phenol-wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…It should be noted that several studies reported the presence of a cell wall-associated polysaccharide of P. acnes that can partially be extracted by phenol extraction [35-37]. Such a cell wall polysaccharide was further described as a lipidated macroamphiphile; this lipoglycan cell envelope component of P. acnes was found to have a lipid anchor and a polysaccharide moiety containing mannose, glucose and galactose, and probably diaminohexuronic acid [38]. We strongly suspect that the lipoglycan of P. acnes is distinct from the EPS of P. avidum .…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that several studies reported the presence of a cell wall-associated polysaccharide of P. acnes that can partially be extracted by phenol extraction [35-37]. Such a cell wall polysaccharide was further described as a lipidated macroamphiphile; this lipoglycan cell envelope component of P. acnes was found to have a lipid anchor and a polysaccharide moiety containing mannose, glucose and galactose, and probably diaminohexuronic acid [38]. We strongly suspect that the lipoglycan of P. acnes is distinct from the EPS of P. avidum .…”
Section: Discussionmentioning
confidence: 99%
“…First, bacterial-derived proteins, such as lipoglycans of the Gram-positive cell envelope or the heat shock proteins are known TLR ligands. To date, several P. acnes cell envelope components such as GroEL and DnaK (Farrar et al, 2000) or lipoglycans (Whale et al, 2004) have been identified. Moreover, Graham et al (2004) have showed that P. acnes GroEL is able to upregulate the pro-inflammatory cytokine production of keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In response to bacterial lipoteichoic acid (LTA) and diacylated lipoproteins, CD36 associates with TLR-2/6 [24],[27]. Although it does not express LTA, P. acnes expresses a closely related amphiphilic antigen, a lipoglycan containing mannosyl, glucosyl, galactosyl residues, and an amino sugar, diaminohexuronic acid [28],[29]. We observed that, blocking CD36 with a monoclonal anti-CD36 antibody in P. acnes -stimulated keratinocytes, significantly decreases both the level of O 2 •− and that of IL-8.…”
Section: Discussionmentioning
confidence: 99%